THE EFFECT OF HERRINGBONE TECHNIQUE ON STUDENTS’ READING COMPRIHENSION OF RECOUNT TEXT (A Study at the Eighth Grade Students of SMP Negeri 1 Angkola Timur) - Tiyana Liza Gultom (JURNAL LINER (Language Intelligence and Educational Research), 2020)
The objectives of the research are to find out: 1) the extent of the application of herringbone on students’ reading comprehension of recount text, 2) the extent of students’ reading comprehension of recount text before and after using herringbone technique, 3) whether there is any significant effect of herringbone technique on students’ reading comprehension of recount text at the eighth grade students of SMP Negeri 1 Angkola Timur. This research uses experimental method. The population is all the eighth grade students which are devided into five classes and total are 107 students. The sample consist of 21 students by using purposive sampling. The technique of collecting data is used observation and test. After collecting the data, the mean of application description of herringbone technique is 3,60. It is catagorized “Very Good”. The students’ reading comprehension of recount text before using herringbone technique is 63,23. It is categorized “Enough”. The students’ reading comprehension of recount text after using herringbone technique is 81,71. It is catagorized “Good”. The calculation of t-test formula is 9,13, and the t-table is 2,09. It means that there is a significant effect of herringbone technique on students’ reading comprehension of recount text at the eighth grade students of SMP Negeri 1 Angkola Timur.